Women Stereotype On Tv Talk Show - Sofia Aunul, Sofia Aunul (2015)
Of the many influences on how we view men and women, media are the most pervasive and one of the most powerful. Woven throughout our daily lives, media insinuate their messages into our consciousness at every turn. All forms of media communicate images of the sexes, many of which perpetuate unrealistic, stereotypical, and limiting perceptions. Television as one of the mass media portrays women stereotype as “Ini Talk Show” program does. “Ini Talk Show” is like any other talk shows—the host, topic, and guests. But “Ini Talk Show” has slight differences on the setting such as they put a house living room concept. Besides the host, topic and guests, there are some characters shown there such as Sule as an intern host, Andre as the co host, Saswi as Sule’s uncle, Parto as the house security officer (Satpam), Maya Septa as the a domestic help and Yurike Prastika as Sule’s mother. This research is descriptive and qualitative approach using John Fiske Semiotics which follows three types of analyses: reality level, representation level and ideology level. The reality level includes appearance, dress, make up, environment, behavior, speech, gesture and expression. Representation level is about technical code such as camera techniques, lighting, editing, music and sound transmitted conventional code representation which shape narration, conflict, character, action, dialog, setting and casting. And the last level is ideology level. This research shows that “Ini tak Show” program portrays women stereotype in the media. The ideology revealed from this program is patriarchy where Man (Sule-the main host) always gives orders and sometimes give envelopes (money) to other characters showing the power relation. And women are represented by the two characters: Maya the domestic help who is dutiful and submissive character that always does what she is told to do and Mami the host mother who likes spending money on glamorous fashion.